Pengaruh Peran Tenaga Kesehatan, Peran Keluarga, Kondisi Kesehatan Fisik, Dan Motivasi Terhadap Kecemasan Pada Ibu Menopause - Mega Wati; Hida Yani (Citra Delima Scientific journal of Citra Internasional Institute, 2021)
Anxiety ahead of menopause is a form of concern due to changes in both physical and psychological changes, which are characterized by cognitive, affective, somatic, and motoric symptoms. Maternal anxiety during menopause will cause problems in the sexual life of husband and wife, physical and psychological symptoms such as excessive sweating and feeling of uselessness because it can't bear children anymore. The purpose of this study to determine the influence of the role of health workers, family roles, physical environmental conditions and motivation to the anxiety of menopausal women in the Village Pagarawan Year 2018. The study design using cross-sectional. Methods of analysis using Smart PLS 2.0 and SPSS 18. The population of menopausal women as much as 68 people. The results of hypothesis testing with Structural Equation Model (SEM) with the smart pls method resulted in research findings, namely the role of health personnel (17.02%), family role (11.79%), physical health condition (26.18%) and motivation (26, 29%). The direct effect of menopausal mother's anxiety was 81.28% and the indirect effect was 1.44%. The total direct and indirect effects of postmenopausal anxiety were 82.72%. Motivation is a dominant factor that greatly affects the anxiety of menopausal women. Researchers suggest that all sectors work together to motivate mothers from premenopausal preparations to mothers can adapt to menopause.